Diagnosis of an emerging Nocardia species infection by MALDI-TOF in a patient with tuberculosis - Cámara Reyes, Ramón R. (2024)
Nocardia infections exhibit diverse clinical manifestations, pulmonary nocardiosis (PN) is the most common. In countries with a high burden of MDR TB such as Peru, co-infection with Nocardia is possible. We report the case of a 91-year-old male with cough, malaise, and weight loss, initially treated for pulmonary tuberculosis (sputum BK positive) without improvement. Subsequent testing with MALDI-TOF identified Nocardia cyriacigeorgica in sputum, confirming coinfection with Mycobacterium tuberculosis sensitive to rifampin detected through real-time PCR. Rapid diagnostic tools such as PCR and MALDI-TOF enhance diagnostic precision; however, their interpretation must consider individual risk factors to avoid overtreatment and ensure an appropriate therapeutic regimen.